2022
DOI: 10.15439/2022f191
|View full text |Cite
|
Sign up to set email alerts
|

Learning edge importance in bipartite graph-based recommendations

Abstract: In this work, we propose the P3 Learning to Rank (P3LTR) model, a generalization of the RP3Beta graphbased recommendation method. In our approach, we learn the importance of user-item relations based on features that are usually available in online recommendations (such as types of user-item past interactions and timestamps). We keep the simplicity and explainability of RP3Beta predictions. We report the improvements of P3LTR over RP3Beta on the OLX Jobs Interactions dataset, which we published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We published an analogous dataset from a different period on Kaggle. 4 We conducted a more comprehensive analysis of this dataset in our previous work [16].…”
Section: Online A/b Testmentioning
confidence: 99%
See 1 more Smart Citation
“…We published an analogous dataset from a different period on Kaggle. 4 We conducted a more comprehensive analysis of this dataset in our previous work [16].…”
Section: Online A/b Testmentioning
confidence: 99%
“…They usually make use of information about previous interactions between users and items not only when training the models, but also when producing recommendations for users. It has been observed that the most recent user interactions are usually the most important for producing recommendations [4].…”
Section: Introductionmentioning
confidence: 99%